Infantile epileptic encephalopathy, transient choreoathetotic movements, and hypersomnia due to a De Novo missense mutation in the SCN2A gene - Hackenberg, Annette; Baumer, Alessandra; Sticht, Heinrich; Schmitt, Bernhard; Kroell-Seger, Judith; Wille, David; Joset, Pascal; Papuc, Sorina; Rauch, Anita; Plecko, Barbara (Neuropediatrics, 2014)
Mutations of the SCN2A gene have originally been described in association with benign familial neonatal-infantile seizures (BFNIS). Recently, single patients with more severe phenotypes and persisting epileptic encephalopathies have been recognized. We report the case of a girl with severe infantile onset epileptic encephalopathy and a de novo missense mutation in the SCN2A gene (c.4025T > C/ = ; p.L1342P/ = ), who presented with a transient choreatic movement disorder, hypersomnia, and progressive brain atrophy. Whole exome sequencing did not reveal any other disease causing mutation. Our patient contributes to the expanding phenotypic spectrum of SCN2A-related disorders and underlines the importance of genetic workup in epileptic encephalopathies.
EVALuna2:26283